100 years of Bacillus Calmette-Guérin immunotherapy: from cattle to COVID-19 - Lobo, Niyati; Brooks, Nathan A; Zlotta, Alexandre R; Cirillo, Jeffrey D; Boorjian, Stephen; Black, Peter C; Meeks, Joshua J; Bivalacqua, Trinity J; Gontero, Paolo; Steinberg, Gary D; McConkey, David; Babjuk, Marko; et al. (Nature reviews. Urology, 2021)
Bacillus Calmette-Guérin (BCG) is the most widely used vaccine worldwide and has been used to prevent tuberculosis for a century. BCG also stimulates an anti-tumour immune response, which urologists have harnessed for the treatment of non-muscle-invasive bladder cancer. A growing body of evidence indicates that BCG offers protection against various non-mycobacterial and viral infections. The non-specific effects of BCG occur via the induction of trained immunity and form the basis for the hypothesis that BCG vaccination could be used to protect against the severity of coronavirus disease 2019 (COVID-19). This Perspective article highlights key milestones in the 100-year history of BCG and projects its potential role in the COVID-19 pandemic.